Within-Population Variations in Home Range Use and Food Patch Use of Japanese Macaques: A Perspective of Intergroup Hostility - Kurihara, Yosuke; Hanya, Goro (Folia primatologica, 2018)
Behavioral mechanisms of intergroup feeding competition remain unclear, despite its importance as a benefit of group living. Japanese macaques in the coastal and highland forests of Yakushima, Japan, are ideal study subjects because the intensity of intergroup feeding competition differs without phylogenetic effects. We aimed to test whether macaques modify home range use and food patch use in response to the location-specific risk of intergroup encounters. Using behavioral data from 3 groups, we examined the border avoidance and the effects of food patch location on food patch use. All 3 groups used the border less frequently than expected from its area. In the coastal forest characterized by frequent intergroup aggression, the smaller subordinate group, not the larger dominant group, increased the number of co-feeding individuals along the border. This response might reduce the potential costs of intergroup aggression. Feeding duration in one patch, visual scanning, and co-feeding with adult males did not depend on food patch location for the 2 groups. In contrast, the highland group did not modify food patch use along the border owing to the low risk of intergroup encounters. Our results highlight the importance of intergroup hostility as a social factor affecting animal behavior.